Head Start and the Distribution of Long Term Education and Labor Market Outcomes - Monique de Haan; Edwin Leuven (Institute for the Study of Labor (IZA), 2016)
In this paper we investigate the effect of Head Start on long term education and labor market outcomes using data from the NLSY79. The contributions to the existing literature on the effectiveness of Head Start are threefold: (1) we are the first to examine distributional effects of Head Start on long term outcomes (2) we do not rely on quasi-experimental variation in Head Start participation but instead perform a nonparametric bounds analysis that relies on weak stochastic dominance assumptions and (3) we consider education and labor market outcomes observed for individuals in their early 30s. The results show that Head Start has a statistically significant positive effect on years of education, in particular for women, blacks and Hispanics. For wage income we also find evidence that Head Start has beneficial impacts, with effects located at the lower end of the distribution.
Keywords: H52; I21; J13; J24; J31; 330; Head Start; early intervention; long term outcomes; partial identification